CTGF promotes articular damage by increased proliferation of fibroblast-like synoviocytes in rheumatoid arthritis. (3rd July 2016) - Ding, S; Duan, H; Fang, F; Shen, H; Xiao, W
Abstract : Objectives : Fibroblast-like synoviocytes (FLS) are a major component of the hyperplastic synovial pannus, which aggressively invades cartilage and bone during the course of rheumatoid arthritis (RA). Connective tissue growth factor (CTGF or CCN2) is a product of a growth factor-inducible immediate early gene and is involved in cell adhesion, proliferation, and differentiation. However, the role that CTGF plays in FLS proliferation has remained undetermined. The aim of this study was to identify the role of CTGF in regulating the proliferation of FLS derived from patients with RA. Method : CTGF levels in serum and synovial fluid (SF) were determined by enzyme-linked immunosorbent assay (ELISA). Expression of CTGF in FLS was determined using reverse transcription polymerase chain reaction (RT-PCR). FLS proliferation stimulated by CTGF was measured by thymidine incorporation. The influence of CTGF small interfering RNA (siRNA) on FLS apoptosis was detected by flow cytometry. Results : CTGF was overexpressed in serum and SF samples from RA patients compared with samples from normal controls. Elevated levels of CTGF in RA SF promoted the proliferation of FLS. Furthermore, in samples from RA patients, CTGF was found to protect FLS from apoptosis and to sustain the expression of survivin in FLS. The expression of CTGF in FLS can be up-regulated by tumour necrosis factor (TNF)-α. Conclusions : Our findings indicate that CTGF plays a crucial role in the proliferation of FLS in RA and probably contributes to synovial lining cell hyperplasia and eventually to joint destruction in patients with RA.